LOCAL WISDOM VALUES IN ENGLISH LEARNING BY USING JOYFUL LEARNING AT PIAUD UMMUL HABIBAH IN KLAMBIR 5 KEBUN VILLAGE - Sari, Indah; Julia Nuraisyah , Adinda Dwi Fanny, Rahayu Dwi Utami, Rika Widya, (Linguistik : Jurnal Bahasa dan Sastra, 2024)
The integration of local culture in early childhood education is very important to help children understand and appreciate their own cultural identity, build self-confidence and pride in cultural background, shape children's character, develop social skill ability, stimulate their creativity and self-expression, provides a holistic approach that covers the cognitive, emotional and social aspects, and encourage innovation that respects tradition. This study aimed to describe the values of local wisdom in learning English in early childhood at PIAUD Ummul Habibah Desa Klambir 5 Kebun, Hamparan Perak sub-district. This study used a qualitative descriptive method and the technique of data collection by using semi-structured interview to 3 teachers at the PIAUD. Then, the technique of data analysis applied Miles, Huberman and Saldana’s steps. The results of this study indicated that the values of local wisdom applied in learning English using joyful learning are 1) the application of religious values in the form of prayer activities and reading Al-Quran surahs before starting learning activities, 2) helping each other in the learning process, 3) cooperation in completing tasks, and 4) respect for learning outcomes. This study concluded that integrating local wisdom values in English language learning using joyful learning could be an effective approach for introducing local culture, increasing understanding and mastery of English, and developing student character. It is hoped that the results of this study could contribute to the development of an English language learning model that has an insight into local wisdom and uses a fun learning approach.